The Polish transition programme at mid-1991: Stabilisation under threat - Jan Winiecki (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
Monetary restraint in Poland does not operate in the expected manner under the conditions of predominant state ownership of both banks and industrial enterprises. With effective owners' control being prohibitively costly in the state-owned firms, "nobody's" banks continue their old lending pattern to large state-owned enterprises regardless of the latters' creditworthiness and profitability. "Nobody's" enterprises accustomed to soft budget constraint are not deterred by high interest rate levels. Under these circumstances macroeconomic restraint does not select the best enterprises but in fact does the reverse: Least efficient large enterprises survive, while smaller but more efficient ones starved of credits are threatened with bankruptcy. Inability to cope effectively with the legacy of the Soviet-type economy is compounded by autonomous policy errors. Apart from too nervous reactions to monthly changes in the inflation rate, the major mistake has been the timing and scale of tightening monetary policy. The sharp increases in the interest rate were effected almost weeks before the major demand reduction for Polish products resulting from the expected changes in trade with the Soviet Union. As a result the economy received a strong recessionary blow from monetary policy that preceded another major blow from the fall in foreign demand. Inevitably the economy went into a recession that did not end by June 1991 while inflation continued.
Keywords: 330; Wirtschaftspolitik; Inflation; Systemtransformation; Polen